(3GdJMUjd dahGFO cJGH GdJaUjds - (3CHh GdYHGS CMeO Hf YeGQ Hf CHj GdYHGS GdebQF GdegQhjs ((3Ydi Hf eMeO Hf YHO GdQMef s)
(3ChdgG (B:s
(3Gdbhd ai bhdg JYGdi jG Cgd GdcJGH bO LGAce QShdfG jHjf dce Edi bhdg (B( (3acGdkG ef Gdgd hGddg YRjR Mcje (B) (3ef ShQI GdeGFOI s
(3BNQgG (B:s
(3jfJgi HJaSjQ ShQI GdMLQ jdjI ai GdSaQ GdKGdK ShQI GdfMd s
(3GdfSNI HgG MhGTs
(3fSNI fajSI LOkGs
(3dNRGfI Gdedc GdLdjd CHj GdLjT eLGgO s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs